Upward bound : a novel [large type] - Brown, Woody (Random House Large Print, 2026)
"Upward Bound is not a place anyone dreams of spending their days. The dreary adult daycare center for Los Angeles's disabled community is, for many of its clients and staff, a place of last resort. This includes Carlos, a young aide who lost his mother as a boy and now works there alongside his beloved sister Mariana; Jorge, the gentle nonspeaking giant whom Carlos seeks to befriend (and prevent from escaping); Tom, a beautiful young man with cerebral palsy, who pines for Ann, the summer lifeguard at the center's pool who feels out of her depth; then there's Dave, Upward Bound's director who came to L.A. to pursue an acting career but now channels his passion into staging an overly ambitious holiday show starring the center's irrepressible clients. Framing these intertwined narratives--and connecting them in surprising, shattering ways--is the riveting and sometimes ironic testimony of Walter, a recent community college graduate who, after a family tragedy, must return to the company of his disabled peers. In Upward Bound, Woody Brown has created an indelible, authentic, and profoundly moving group portrait of autism and other disabilities, all illuminated by his empathy, sly sense of humor, and enormous gifts as a novelist. With remarkable sophistication, insight, and creativity, Brown depicts a community too-often invisible in literature and society. Filled with characters you won't soon forget, Upward Bound will inspire and touch you, teaching you as much about yourself as the tender, miraculous world behind the center's doors"--Amazon website.